Effects of acetate on cerebral blood flow, systemic inflammation, and behavior in alcohol use disorder. (16th April 2021) - Tanabe, Jody; Neff, Sarah; Sutton, Brianne; Ellis, Sam; Patten, Luke; Brown, Mark S.; Hoffman, Paula L.; Tabakoff, Boris; Burnham, Ellen L.
Abstract: Background: Alcohol use disorders (AUDs) are associated with altered regulation of physiological processes in the brain. Acetate, a metabolite of ethanol, has been implicated in several processes that are disrupted in AUDs including transcriptional regulation, metabolism, inflammation, and neurotransmission. To further understand the effects of acetate on brain function in AUDs, we investigated the effects of acetate on cerebral blood flow (CBF), systemic inflammatory cytokines, and behavior in AUD. Methods: Sixteen participants with AUD were recruited from a nonmedical, clinically managed detoxification center. Each participant received acetate and placebo in a randomly assigned order of infusion and underwent 3T MR scanning using quantitative pseudo‐continuous arterial spin labeling. Participants and the study team were blinded to the infusion. CBF values (ml/100 g/min) extracted from thalamus were compared between placebo and acetate using a mixed effect linear regression model accounting for infusion order. Voxel‐wise CBF comparisons were set at threshold of p  < 0.05 cluster‐corrected for multiple comparisons, voxel‐level p  < 0.0001. Plasma cytokine levels and behavior were also assessed between infusions. Results: Fifteen men and 1 woman were enrolled with Alcohol Use Disorders Identification Test (AUDIT) scores between 13 and 38 with a mean of 28.3 ± 9.1. Compared to placebo, acetate administration increased CBF in the thalamus bilaterally (Left: 51.2 vs. 68.8, p  < 0.001; Right: 53.7 vs. 69.6, p  = 0.001), as well as the cerebellum, brainstem, and cortex. Older age and higher AUDIT scores were associated with increases in acetate‐induced thalamic blood flow. Cytokine levels and behavioral measures did not differ between placebo and acetate infusions. Conclusions: This pilot study in AUD suggests that during the first week of abstinence from alcohol, the brain's response to acetate differs by brain region and this response may be associated with the severity of alcohol dependence.